2023
DOI: 10.3389/fphar.2023.1136114
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of regorafenib and rosuvastatin in colorectal cancer

Abstract: Introduction: Colorectal cancer is one of the most prevalent life-threatening malignant tumors with high incidence and mortality. However, the efficacy of current therapeutic regimens is very limited. Regorafenib has been approved for second- or third-line treatment of patients who are refractory to standard chemotherapy diagnosed with metastatic colorectal cancer, but its clinical efficacy needs to be further improved. Accumulating evidence demonstrates that statins also possess potent anticancer activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These reports underline the importance of evaluating interactions between ATO and REG. Yuan et al [38] found that the combination of rosuvastatin and REG had a synergistic effect, which may be a new standard of colorectal cancer treatment.…”
Section: The Influence Of Reg On the Pharmacokinetics Of Ato 2-oh Ato...mentioning
confidence: 99%
“…These reports underline the importance of evaluating interactions between ATO and REG. Yuan et al [38] found that the combination of rosuvastatin and REG had a synergistic effect, which may be a new standard of colorectal cancer treatment.…”
Section: The Influence Of Reg On the Pharmacokinetics Of Ato 2-oh Ato...mentioning
confidence: 99%
“…Statins may be considered as targeted therapy for CRC ( Shailes et al, 2022 ). Meanwhile, in the treatment, statins can enhance the anticancer activity of the chemotherapeutic drug oxaliplatin, enhance the sensitivity of radiotherapy for CRC and synergize the antitumor effect of the targeted drug regorafenib, which may arise from the weakening of stemness and drug resistance of CRC cells by statins ( Karagkounis et al, 2018 ; Gao et al, 2021 ; Gonçalves et al, 2021 ; Tsubaki et al, 2023 ; Yuan et al, 2023 ). Pravastatin, a metabolite of intestinal flora, can promote interleukin (IL)-13 release from type Ⅱ innate lymphocytes through IL-33 signaling, which has been shown to promote self-renewal of pluripotent intestinal stem cells at the base of intestinal crypts ( Zhu et al, 2019 ; Deng et al, 2021 ).…”
Section: Drug Repurposing and Microbiota In Colorectal Cancermentioning
confidence: 99%